PERBEDAAN TINGKAT KOHESIVITAS TIM ANTARA CABANG OLAHRAGA SEPAK BOLA, BOLA VOLI DAN BOLA BASKET - Dimyati Dimyati (LPPM UNY, 2003)
Abstract This research in general has the aim to know the difference of cohesiveness level between the sport of soccer, volleyball, and basketball. The special aim, which will be known the branches of sports mentioned above, that is soccer, volleyball and basketball, has the strongest of cohesiveness level. This research of population is the players of soccer, volleyball and basketball, which combine in the several groups. Which are found in the Daerah Istimewa Yogyakarta. The taking of technical sample is cluster random sampling. The total sample in the research is 114 players of soccer 38 persons, volleyball 38 persons and basketball 38 persons. Method and instrument used are questionnaire method and modified Likert scale. The team Cohesiveness Questionnaire (TCQ) instrument is used to find out the team cohesiveness. The result of counting which based on the one way variant analysis is found the value of F=4.991 and p 0.008 this know that there is difference of team cohesiveness of significant level among the sport ranches of soccer, volleyball and basketball. The result of analysis by using T-test shows that the team branch of sports has differences of level of cohesiveness, which is highest as will as the team of basketball branch. So the research has concluded that (1) there is difference of level cohesive among the branches of soccer, volleyball and basketball, (2) the branch of basketball sport his level of cohesiveness, which is comparative with the bernacle’s volleyball and soccer. Keywords: cohesiveness, soccer, volleyball and basketball